The Importance of Instrumental Motivation among Students in Teaching English as Foreign Language (TEFL) Process - Anggitaria Siahaan; Ardayati Ardayati; Maria Ramasari (EDUCAFL : Journal of Education of English as Foreign Language, 2022)
The aim of this research was to identify the category of students’ instrumental motivation and to describe the importance of instrumental motivation in the English learning process of English as Foreign Language (EFL) students. A quantitative descriptive method was used in this research to analyze the data. The subject of this research was 28 EFL students from the fourth semester students of English Education Study Program at STKIP-PGRI Lubuklinggau. The researchers used questionnaire and interview as instruments in obtaining the data investigation. Techniques for analysis the data were identification, calculation, classification, description and conclusion. The result of this research revealed that the students’ instrumental motivation was in strong category with total average 77.93 %. It meant that the categories level of motivation among the fourth semester students of English Education Study Program at STKIP-PGRI Lubuklinggau to study English is strong motivation. This proved that students had a very strong level of instrumental motivation. The students believed that a good way will be a good thing and motivation is enough to help them. With the aim of passing the exam, getting a job, having a better career, and getting a better future was their motivation in learning English. Automatically, it was proved that they had instrumental motivation, and it made them more motivated to achieve their goals though they learn English as foreign language. It indicated that instrumental motivation had an important role in the English learning process to the EFL students in English education study program at STKIP-PGRI Lubuklinggau. In summary, instrumental motivation was one of the factor that influenced the students to be success in learning a foreign language (English). This motivation was also very helpful in English learning process, because students who had this motivation show that they wanted to learn English seriously.